Aplicação da equação da onda na análise do comportamento de estacas cravadas - Nakao, Ricardo (1981)
This thesis presents initially a review of the literature on the application of the wave equation to the prediction of pile behaviour. As part of this review, the theoretical basis of the method, together with suggestions for its implementation is presented. With the aid of motion pictures, the behaviour of steel piles during driving (for the construction of the Rio de Janeiro Subway) was recorded. This records provided data for the wave equation analysis and the results of these predictions were compared with those of load tests. Comparisons with driving formulae were also made. The numerical solution scheme by E. A. L. SMITH (1960) was discused together with more recent proposals.